Preimplantation and postimplantation therapy for the treatment of reproductive failure - Pratap Kumar; Siddharth Mahajan (Wolters Kluwer Medknow Publications, 2013)
Treatment of patients with recurrent pregnancy losses and recurrent implantation failure can be instituted only when the underlying etiology is determined. Embryo-secreted preimplantation factor (PIF) is essential for implantation and adequate trophoblastic invasion. Deficiency of PIF affects the outcome of the pregnancy leading to recurrent pregnancy losses. Synthetic PIF modulates the outcome of the pregnancy decreasing the incidence of recurrent implantation failure and recurrent pregnancy losses. In this article a thorough search is done regarding the data published for diagnoses of reproductive failure and its treatment. The effect of immunoglobulin (Ig), intralipid, heparin, aspirin, progesterone, estrogen, and granulocyte colony stimulating factor (G-CSF) is taken into consideration. Heparin, aspirin, and progesterone have successfully shown to decrease the incidence of recurrent pregnancy loses; whereas G-CSF, intralipids, estrogen, and Igs have shown success in the treatment of the recurrent implantation failure and recurrent pregnancy failure. The pregnancies treated with Igs and intralipids showed equal outcome when evaluated and compared. The place of intralipid in reducing natural killer (NK) cells has been discussed.